Internal and external load characteristics in professional female cyclists during highly successful and less successful seasons - Roete, A. J.; van Erp, T.; Elferink-Gemser, M. T.; Kempe, M.; Lamberts, R. P. (International Journal of Sports Physiology and Performance, 2025)
Purpose: This exploratory study aimed to determine and compare the external and internal training and racing load characteristics of female professional cyclists during "highly successful" and "less successful" seasons.